Ultrasonic characterization of metals from selective laser melting process - Lim, Jonthan Jun Xun (Nanyang Technological University, 2024)
Selective Laser Melting (SLM) technology has gained significance in Additive Manufacturing (AM), enabling the production of detailed and customized components. However, the structural integrity and quality of SLM-produced parts are important factors to be considered. This study explores the application of ultrasonic techniques for the non-destructive evaluation of samples manufactured through the SLM process. Ultrasonic waves are employed to investigate the internal features, such as porosity in the SLM-produced samples. The research uses ultrasonic methods to provide insights into the microstructure and mechanical properties of the samples. The ultrasonic tests aim to enhance the understanding of the relationships between ultrasound scattering induced attenuation and mechanical properties of SLM-created parts, allowing for optimisation of manufacturing conditions for improved part quality. The findings contribute to the broader understanding of ultrasonic attenuation relationship with porosity and mechanical properties of a material. This study will lay the groundwork for enhanced quality control and reliability in SLM-produced components.